Cooling efficiency in furnace design - Gonzalez-Ojeda, Roberto; Quintana Hernández, María José; Ruiz Bustinza, Iñigo; García Carcedo, Fernando; Barbés, Miguel Ángel; Florentina Barbés, María (Universidad Nacional de Colombia, Facultad de Minas, 2013)
During melting, reduction or thermal treatment of a steel charge, the input of energy (either chemical or electrical) is indispensable to guarantee the viability of the process. Under these circumstances, it will be reasonable to design the furnace lining in such a way that heat loss through the walls is minimized. Nevertheless, it can be proved that, for some situations, it is more efficient to withdraw as much heat as possible from the walls than trying to thermally isolate the system. The work presents recommendations for the design of walls and cooling systems in furnaces obtained by quantitative analysis of temperatures reached in specific locations of the furnace using the nodal wear model. The analysis indicates that the wear process of the lining may be controlled if all the elements that intervene in the process are known.

Durante la fusión, la reducción o el tratamiento térmico de una carga de acero, es indispensable suministrar energía (ya sea química o eléctrica) para garantizar la viabilidad del proceso. Bajo estas circunstancias será razonable diseñar el recubrimiento de los hornos de forma que la pérdida de calor a través de las paredes sea mínima. Sin embargo, se puede demostrar que, para algunas situaciones, es más eficiente retirar la mayor cantidad de calor posible de las paredes que intentar aislar térmicamente el sistema. El trabajo presenta recomendaciones para el diseño de paredes y sistemas de refrigeración en hornos, obtenidas mediante el análisis cuantitativo de las temperaturas que se alcanzan en posiciones específicas del horno y usando el modelo de desgaste nodal. El análisis indica que el mecanismo de degradación del refractario puede ser controlado si se conocen todos los elementos que intervienen en el fenómeno.
Eficiencia de la refrigeración en el diseño de hornos
Keywords: Metallurgy; Furnaces; Heat loss; Lining; wear